Genome analysis of Desulfotomaculum gibsoniae strain GrollT a highly versatile Gram-positive sulfate-reducing bacterium. Issue 3 (November 2014) - Kuever, Jan; Visser, Michael; Loeffler, Claudia; Boll, Matthias; Worm, Petra; Sousa, Diana; Plugge, Caroline; Schaap, Peter; Muyzer, Gerard; Pereira, Ines; Parshina, Sofiya; Goodwin, Lynne; et al.
Abstract Desulfotomaculum gibsoniae is a mesophilic member of the polyphyletic spore-forming genusDesulfotomaculum within the familyPeptococcaceae . This bacterium was isolated from a freshwater ditch and is of interest because it can grow with a large variety of organic substrates, in particular several aromatic compounds, short-chain and medium-chain fatty acids, which are degraded completely to carbon dioxide coupled to the reduction of sulfate. It can grow autotrophically with H2 + CO2 and sulfate and slowly acetogenically with H2 + CO2, formate or methoxylated aromatic compounds in the absence of sulfate. It does not require any vitamins for growth. Here, we describe the features ofD. gibsoniae strain GrollT together with the genome sequence and annotation. The chromosome has 4, 855, 529 bp organized in one circular contig and is the largest genome of all sequencedDesulfotomaculum spp. to date. A total of 4, 666 candidate protein-encoding genes and 96 RNA genes were identified. Genes of the acetyl-CoA pathway, possibly involved in heterotrophic growth and in CO2 fixation during autotrophic growth, are present. The genome contains a large set of genes for the anaerobic transformation and degradation of aromatic compounds, which are lacking in the other sequencedDesulfotomaculum genomes.